Cross-cultural biology teaching using next generation science standards - Jimenez, Jason G. (Animo Repository, 2023)
STEM professionals have played a crucial role in driving national development forward. The STEM workforce in the Philippines has been declining due to the need for improved quality of education. Therefore, there was still work to be done to enhance science competencies. In order to address the issue, our goal was to implement a novel approach to enhance the learning of Biology. We conducted a study on teaching biology using a cross-cultural approach. Our main objectives were to identify (a) the different types of knowledge and skills in biology, (b) the feedback received during the development of lessons, (c) the exchange of insights through lesson study, (d) the validation of learning exemplars, (e) the performance of students during the implementation of teaching, and (f) the experiences of students to understand their sensemaking process. The study employed a grounded theory design to examine a new approach to non-Mendelian genetics. Three study phases were determined. In the first phase, discourse analysis was conducted to examine and compare the similarities, differences, and educational opportunities in science education. Another method for lesson development is through the use of lesson study. The third aspect focused on the implementation of teaching. The use of qualitative data was essential in this research. It allowed us to analyze policies, document feedback and experiences during lesson development, and engage with students to gather valuable insights into their learning experiences. Based on our research, we discovered that several factors can enhance science learning. These include retrieving prior knowledge, creating meaningful learning experiences, improving memory and retention, fostering engagement in learning, and developing critical thinking skills. This study offered an opportunity for instructors to enhance their professional development by facilitating the sharing of STEM knowledge. In addition, the framework introduced a distinct methodology for developing science teaching and learning processes. Therefore, this will lead to the development of a future generation of STEM students.